Product Development: Yellow Pumpkin Donuts And RPO (Red Palm Oil) For School-Age Children - Qurratu Aini; Dewi Kusumawati; Hanna Nurjanah (Journal of Applied Food and Nutrition, 2022)
Background: Nutritional problems are crucial things to be concerned about, especially for children. Children are still growing, so their nutritional intake needs to be considered. Vitamin A deficiency still often occurs in children, even though vitamin A has a significant role in the child's growth process. Food sources that contain good sources of pro-vitamin A but are never used properly are pumpkin and Red Palm Oil (RPO). This study aims to make a product in the form of donuts, the type of snack that is of interest to children, and increase the added value of pumpkin and RPO.  Methods: The research method used is Pure Experimental, which consists of several activities, starting with product trial, product manufacture, hedonic test, and product quality test. Data analysis was performed using Ms. Excel 2016.Result: The results of the overall hedonic test of the product are 4.1, which means that the product is favored by the panelists. while results of the hedonic quality test show that the product has a golden yellow color, a pleasant aroma, a sweet taste, a slightly soft texture, and a weak after taste.